Effects of global warming on sex ratios in fishes. Issue 3 (27th July 2020) - Geffroy, Benjamin; Wedekind, Claus
Abstract: In fishes, sex is determined by genetics, the environment or an interaction of both. Temperature is among the most important environmental factors that can affect sex determination. As a consequence, changes in temperature at critical developmental stages can induce biases in primary sex ratios in some species. However, early sex ratios can also be biased by sex‐specific tolerances to environmental stresses that may, in some cases, be amplified by changes in water temperature. Sex‐specific reactions to environmental stress have been observed at early larval stages before gonad formation starts. It is therefore necessary to distinguish between temperature effects on sex determination, generally acting through the stress axis or epigenetic mechanisms, and temperature effects on sex‐specific mortality. Both are likely to affect sex ratios and hence population dynamics. Moreover, in cases where temperature effects on sex determination lead to genotype–phenotype mismatches, long‐term effects on population dynamics are possible, for example temperature‐induced masculinization potentially leading to the loss of Y chromosomes or feminization to male‐biased operational sex ratios in future generations. To date, most studies under controlled conditions conclude that if temperature affects sex ratios, elevated temperatures mostly lead to a male bias. The few studies that have been performed on wild populations seem to confirm this general trend. Recent findings suggest that transgenerational plasticity could mitigate the effects of warming on sex ratios in some populations.